Design and baseline characteristics of the stroke prevention by aggressive reduction in cholesterol levels (SPARCL) study - Amarenco, Pierre; Bogousslavsky, Julien; Callahan, Alfred S.; Goldstein, Larry; Hennerici, Michael G.; Sillsen, Henrik; Welch, Michael A.; Zivin, Justin A. (Cerebrovascular diseases, 2003)
Evidence suggests that statin therapy reduces the risk of stroke in patients with coronary heart disease (CHD), but its benefit for patients with cerebrovascular disease and no history of CHD remains uncertain. The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) Study is a prospective, multi-centre, double-blind, randomised, placebo-controlled trial designed to evaluate the effects of atorvastatin 80 mg/day in patients who previously experienced a stroke or transient ischaemic attack, but who have no known CHD. A total of 4732 patients have been enrolled, and the data collection phase of the study is expected to be completed by October 2004. SPARCL is the first study primarily designed to prospectively evaluate the effect of statin treatment in secondary stroke prevention.